If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3z-5=z/6-22
We move all terms to the left:
3z-5-(z/6-22)=0
We get rid of parentheses
3z-z/6+22-5=0
We multiply all the terms by the denominator
3z*6-z+22*6-5*6=0
We add all the numbers together, and all the variables
-1z+3z*6+102=0
Wy multiply elements
-1z+18z+102=0
We add all the numbers together, and all the variables
17z+102=0
We move all terms containing z to the left, all other terms to the right
17z=-102
z=-102/17
z=-6
| 3x-5/2=2x+5/3 | | -28-2a=-4(3a+7)+10a | | -8(k+5)=-40-8k | | 9^4x/3^2x=2187 | | -6r-21=-3(6+2r) | | 45-4x=56-5x | | -2/3x-7=1 | | 5x+4=2x=10 | | 4(x-2)-2x=x-9 | | A=3A^(n-1)+1 | | -14-4x=6 | | x-3+2x=0 | | x2+17x+72=12 | | -8(2x-8)-3x=216 | | 5-y-y=3 | | 12+12x=18x+60 | | 7(3x-2)=3(5x-3)+7 | | -5/9+(4/3)-2/3=z | | 7(3m+5)=-91 | | 23=x/5-4 | | 11x-5(x+3)-6x=0 | | x+7/7=8 | | 3+5x=30+4x | | -7/3w=-28 | | 5x+3x-12=x+6 | | 17x-13=106 | | 1/5x+1/3=-15 | | 6(x-7)=-84 | | 2(8-4z)-2(4z+9)=z-9 | | 13x+6=x | | 225=p2 | | −4x+1=-9x+16−9x+16 |